2020
DOI: 10.3390/nu12072060
|View full text |Cite
|
Sign up to set email alerts
|

Might Starvation-Induced Adaptations in Muscle Mass, Muscle Morphology and Muscle Function Contribute to the Increased Urge for Movement and to Spontaneous Physical Activity in Anorexia Nervosa?

Abstract: Severely undernourished and underweight anorexia nervosa (AN) patients typically remain active and mobile. Might such persistent physical activity in AN be supported by specific adaptations in muscle tissue during long term undernutrition? To identify potential differences, studies examining the effects of undernutrition on skeletal muscle mass, muscle morphology and muscle function in healthy humans and in AN patients were reviewed. Adjustments in muscle morphology and function in AN did not differ in substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
2
20
0
1
Order By: Relevance
“…Desires to rest and move, as measured by the 10-item version of the CRAVE, were related to tiredness but not other psychosomatic sensations. Likewise, Casper has found that urges to move, as retrospectively assessed over two weeks, were unrelated to physical and mental tiredness and energy (52, 60). Data from Study 5 support the notion that desires are states.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Desires to rest and move, as measured by the 10-item version of the CRAVE, were related to tiredness but not other psychosomatic sensations. Likewise, Casper has found that urges to move, as retrospectively assessed over two weeks, were unrelated to physical and mental tiredness and energy (52, 60). Data from Study 5 support the notion that desires are states.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the current analysis stage-of-change for exercise predicted wants/desires for movement. However, it would be useful to determine whether those with higher movement desires actually have more energy expenditure (EE) from exercise or non-exercise sources (e.g., occupational activity, active transit, spontaneous physical activity [SPA]) (52, 149) and whether these change over time with chronic training. Movement desires and urges, or what has been termed “appetence”, is magnified with exercise addiction, anorexia, and possibly mania (9, 167).…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…At this juncture, intersecting lines of research strongly suggest that humans possess wants/desires for movement and rest behaviors ( Iqbal et al, 2007 ; Beeler et al, 2012 ; Levitin et al, 2018 ; Williams et al, 2019 ; Casper, 2020 ; Stults-Kolehmainen et al, 2020a ). However, a review study in this special issue reports that “little to no research has been conducted to directly measure craving/desire for PA” ( Stevens et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%